Investigation of the assessment system in primary schools in Turkey and Syria (A comparative study) - Haraki, Omer Abdullah (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to compare assessment systems at the primary level in Turkey and Syria. In this study, the descriptive method was used in investigating and comparing the data, and the study sample was identified in two countries, namely Syria and Turkey, based on the target sample from the Middle East. The results of the study presented many similarities and differences between the educational assessment system in the countries concerned with the study; the educational assessment system of in Turkey is based on the alternative assessment system. In addition, teachers in the classroom apply various measurement methods. The study noticed that the assessment is intense and sequential. Despite this, there are some gaps in tracking modern assessment and measurement systems and the flexibility in their application. For Syria is based on continuous assessment. Despite the Ministry of Education’s recommendation to follow modern measurement methods in the education process, many teachers still follow traditional measurement methods. One of the reasons for this is that the teacher does not pay enough attention and his salary is low. Also, we find a similarity between the assessment policy in Syria and Turkey, in terms of reducing written exams and focusing on performance assessment. In terms of the assessment process, there is a difference as well, but in terms of the strategies and tools used in the assessment, there is almost similarity. In terms of the scoring method, there is also a difference.